Enhancing Nurses' Ethical Knowledge in Hospitals Through the Initiation of Nursing Ethic Navigation and A Nurses' Ethical Guideline E-Book - Citra Hafilah Shabrina; Krisna Yetti; Hanny Handiyani; Shanti Farida Rachmi; Erna Puspita Sari; Roro Tutik Sri Hariyati (Indonesian Journal of Global Health Research, 2025)
Nurses in hospitals often face complex ethical situations; however, there are still gaps in the understanding and application of nursing ethical principles, and a structured, easily accessible ethical guideline is not yet available. This study aims to develop two main solutions Nursing Ethic Navigation (an ethical guideline web search engine) and the Nurses' Ethical Guideline E-Book using John Kotter’s Eight-Step Change Model approach. The method used is a case study conducted at Hospital X during September–October 2024, encompassing problem identification, action planning, implementation, and evaluation. The respondents in this study were the Head Nurse, Primary Nurse, Nursing Department staff, members of the Nursing Committee, and nurses in the IGD-COT unit at Hospital X. Data were collected through interviews, observations, and questionnaires, then analyzed using problem priority scoring and a fishbone diagram to identify root causes as the basis for developing action plans and change strategies. The results showed a significant improvement in nurses’ knowledge, awareness, and ability to apply ethical principles after the intervention. Digital media such as the e-book and web-based tools proved effective as learning platforms and practical references that can be accessed anytime. This study recommends expanding the implementation of ethical guidelines to other service units, supported by managerial involvement and continuous evaluation, to ensure integration into the organizational culture and daily nursing practice.